Effect of Particle Size on the Optical Properties of Silicon‐Vacancy Centers in Nanodiamonds Fabricated by a Detonation Process. Issue 22 (23rd August 2022) - Makino, Yuto; Saito, Yoshiki; Takehara, Hikaru; Tsurui, Akihiko; Okuyama, Naoto; Ashida, Masaaki
Abstract : Nanodiamonds containing silicon‐vacancy centers (SiV‐NDs) are attracting attention as promising fluorescent markers. Recently, the preparation of single‐digit‐nanometer‐sized SiV‐NDs by a detonation process, which can be carried out on a practical scale, has been demonstrated. However, little is known about the effect of these extremely small diamonds fabricated by a detonation process on the electronic state of the SiV centers. In the present study, SiV‐NDs prepared by the detonation process are investigated spectroscopically. It is reported that the extremely small particle size, ≈10 nm, causes an increase of the nonradiative transition probability and an enhancement of the electron–phonon coupling compared with those of typical SiV centers. Because of their electronic states, SiV‐NDs also exhibit a short luminescence lifetime (≈0.56 ns) and a large linewidth (≈14.4 nm) at room temperature. Nevertheless, the fundamental properties of the SiV center, such as the photostability, do not change, irrespective of the particle size. Abstract : Compared with typical silicon‐vacancy (SiV) centers, SiV‐center‐containing nanodiamonds (NDs) fabricated by a detonation process exhibit a shorter luminescence lifetime (0.56 ns) and a broader linewidth (0.0318 eV) at room temperature. These differences are attributed to the extremely small particle size (≈10 nm) of the NDs, which increases the nonradiative transition probability and enhances the electron–phonon coupling.